Diversity of the protease-producing bacteria and their extracellular protease in the coastal mudflat of Jiaozhou Bay, China: in response to clam naturally growing and aquaculture - Liu, Zhiyun; Liu, Guangchao; Guo, Xuzhen; Li, Yang; Ji, Na; Xu, Xingfeng; Sun, Qingjie; Yang, Jie (Frontiers in Microbiology, 2023)
The booming mudflat aquaculture posed an accumulation of organic matters and a certain environmental threat. Protease-producing bacteria are key players in regulating the nitrogen content in ecosystems. However, the knowledge of the diversity of protease-producing bacteria in coastal mudflats is limited. This study investigated the bacterial diversity in the coastal mudflat, especially the protease-producing bacteria and their extracellular proteases, by using culture-independent methods and culture-dependent methods. Clam aquaculture area exhibited a higher concentration of carbon, nitrogen and phosphorus when compared with non-clam area, and a lower richness and diversity of the bacterial community when compared with clam naturally growing area. The major classes in the coastal mud samples were Bacteroidia, Gammaproteobacteria and Alphaproteobacteria. Bacillus-like bacterial community was the dominant cultivated protease-producing group, accounting for 52.94% in non-clam area, 30.77% in clam naturally growing area and 50% in clam aquaculture area, respectively. Additionally, serine protease and metalloprotease were the principal extracellular protease of the isolated coastal bacteria. These findings shed light on the understanding of the microbial involved organic nitrogen degradation in the coastal mudflat, and laid a foundation for the development of novel protease-producing bacterial agents for coastal mudflat purification.